(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Distributed generation (DG) is used to describe a small-scale production of electrical power through integrating different energy technologies. In fact, integration of DG into distribution systems might result in various technical, operational, and economic impacts on distribution systems that can contribute to the enhancement of the security and reliability of the grid. These benefits include decreasing the operation cost, improving the voltage profile and the voltage stability, reducing the losses in the lines as well as eliminating the upgrades of the existing electric networks. In fact, DG units that located close to loads can significantly reduce energy losses in distribution systems. However, DG units need to be allocated correctly and optimally in order to avoid negative effects on electric networks in terms of power losses and voltage profile for the whole network. This paper presents an overview regarding distributed generation effects of electrical networks in terms of technical, environmental and economic benefits.